XVII-XVIII ӘСИРЛЕР ТАРИЙХЫЙ ЎАҚЫЯЛАРЫНЫҢ ТАРИЙХЫЙ ҚОСЫҚЛАРДА СӘЎЛЕЛЕНИЎИ - Турдыев, Б. (FAN va JAMIYAT, 2022)
In the article, there is presented the development and formation of the historical songs of the Karakalpak people includes several periods. Historical songs express the way of life of our people. Historical songs arose and developed in all eras, depending on the way of life of the people.